The post as an utterance: Analysis of themes, compositional forms and styles in blog genre studies. (August 2013) - Primo, Alex; Zago, Gabriela; Oikawa, Erika; Consoni, Gilberto
The blogosphere's heterogeneity has significantly increased in recent years. Thus, the blog-as-diary approach has shown its limitations. Viewing blogs as a genre is also misleading, as it confuses medium and genre. Considering that the studies of blog genres still need further theoretical and empirical investigations, we propose a method to assess blog posts, understood as utterances, the minimal unit of a blog. We then conduct an analysis of two large datasets from 100 Brazilian blogs. Three reviewers read and judged 5218 posts from 50 A-list blogs and 1527 posts from 50 non-A-list blogs, captured in a 30-day period. Posts' compositional form, theme and style were cross-analyzed in and between datasets. Our findings lead to the conclusion that blogs in the A-list group tend to post more and stick to themes that attract audiences. Non-A-list blogs post less and focus on themes of interest to bloggers themselves, not necessarily hype topics.